Atlantic Geological Society: ABSTRACTS, 1991 MINI-SYMPOSIUM "ENVIRONMENTAL GEOLOGY", 1991 COLLOQUIUM "CURRENT RESEARCH IN THE ATLANTIC PROVINCES"

(untitled) (Atlantic Geoscience Society, 1991)
The 1991 Mini-Symposium and Colloquium of the Atlantic Geoscience Society were held at the Wandlyn Motor Inn, Amherst, Nova Scotia on February 8-9,1991. On behalf of the Society we thank David Mossman of Mount Allison University and all others involved in the organization of this excellent meeting. In the following pages we publish the abstracts of talks and poster sessions given at the Mini-Symposium and Colloquium.